2014
DOI: 10.1149/06409.0003ecst
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposition of Nanostructured Tunable Resistance Coatings: Growth, Characterization, and Electrical Properties

Abstract: We have developed atomic layer deposition (ALD) methods to synthesize robust nanostructured composite coatings with tunable resistance comprised of conducting, metallic nanoparticles embedded in an amorphous dielectric matrix. These films are nominally composed of M:Al 2 O 3 where M= W or Mo, and are prepared using alternating exposures to trimethyl aluminum (TMA) and H 2 O for Al 2 O 3 ALD and alternating MF 6 /Si 2 H 6 exposures for the metal ALD. By varying the ratio of ALD cycles for the metal and Al 2 O 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…A similar microstructure was measured for ALD AlMo x F y films deposited under similar conditions. 21 In addition, previous X-ray photoelectron spectroscopy studies on thick ALD AlW x F y films confirmed the metallic nature of tungsten or tungsten carbide, and resistivity values from four-point measurement on the film were found to be 10 –2 Ω·cm, approximately 18 orders of magnitude smaller than that of Al 2 O 3 . 22 However, preliminary X-ray absorption spectroscopy data on AlW x F y -coated particles (not shown) suggest the presence of partially oxidized W δ+ species.…”
Section: Results and Discussionmentioning
confidence: 65%
“…A similar microstructure was measured for ALD AlMo x F y films deposited under similar conditions. 21 In addition, previous X-ray photoelectron spectroscopy studies on thick ALD AlW x F y films confirmed the metallic nature of tungsten or tungsten carbide, and resistivity values from four-point measurement on the film were found to be 10 –2 Ω·cm, approximately 18 orders of magnitude smaller than that of Al 2 O 3 . 22 However, preliminary X-ray absorption spectroscopy data on AlW x F y -coated particles (not shown) suggest the presence of partially oxidized W δ+ species.…”
Section: Results and Discussionmentioning
confidence: 65%
“…Thin ALD W:Al 2 O 3 composite films were prepared in a custom hot-walled viscous flow ALD reactor described elsewhere and using previously published methods. , The precursors TMA (Aldrich, 99%), deionized H 2 O, Si 2 H 6 (Voltaix, 99.999%), and WF 6 (Aldrich, 99.9%) were used and maintained at room temperature. Films were deposited on quartz and p-type Si(100) substrates, and the deposition temperature was maintained at 200 °C.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The material is deposited on the substrate in the form of a monoatomic film surface. ALD can produce a continuous film without pinholes, with excellent coverage, and can control the thickness and composition of the atomic film [ 1 , 2 , 4 , 11 , 13 , 19 , 20 ].…”
Section: Experimental and Methodsmentioning
confidence: 99%